Structure sensitivity and in-situ activation of benzene combustion on Pt/Al2O3 catalysts - Garetto, Teresita Francisca (2001)
The structure sensitivity and in situ activation of benzene combustion on Pt/Al2O3 catalysts of different platinum and chlorine loadings were studied. The catalyst activities were evaluated through both conversion versus temperature (light-off curves) and conversion versus time catalytic tests. The light-off curves shifted to lower temperature with increasing Pt particle size, thereby suggesting that benzene combustion is a structure sensitive reaction. Kinetically-controlled catalytic tests confirmed that benzene oxidation turnover rates are preferentially promoted by larger Pt crystallites. Kinetic studies showed that the reaction orders and the apparent activation energy are not changed by changing the metallic dispersion. Results are explained by considering that benzene oxidation proceeds via a Langmuir–Hinshelwood mechanism which involves the rapid and strong adsorption of benzene on metallic platinum and assumes that the rate constant of oxygen adsorption is very low compared to the rate constant of the surface reaction. The number of PtO bonds of lower binding energy, i.e. the site density of more reactive surface oxygen, increases on larger Pt particles. Low-conversion catalytic tests performed at constant temperature showed that on well-dispersed Pt/Al2O3 catalysts the benzene conversion increases with time, irrespective of the chlorine content on the sample. TEM examination and hydrogen chemisorption measurements suggested that the activity increase parallels a concomitant increase in the platinum particle size. In contrast, sintered samples (platinum dispersions lower than 10%) did not exhibit initial activation periods. It is proposed that the initial in situ activation of well-dispersed Pt catalysts is caused by the sintering of the metallic phase. Hot-spots on the metallic particles together with the presence of gaseous water cause the formation of larger Pt crystallites, even at mild reaction conditions. As a result, the benzene conversion increases with time until the formation of larger steady state Pt particles is completed.